Preventive action of curcumin in experimental acute pancreatitis in mouse - Yu, Wen-Guang (Medknow Publications & Media Pvt Ltd, 2011)
BACKGROUND & OBJECTIVES: Curcuma longa (turmeric) has a long history of use in Ayurvedic medicine as a treatment for inflammatory conditions. The purpose of the present study was to investigate the preventive effects of curcumin against acute pancreatitis (AP) induced by caerulein in mouse and to elucidate possible mechanism of curcumin action. METHODS: Curcumin (50 mg/kg/day) was intraperitoneally injected to Kun Ming male mice for 6 days, followed by injection of caerulein to induce AP. GW9662 (0.3 mg/kg), a specific peroxisome proliferator-activated receptor gamma (PPARγ) antagonist, was intravenously injected along with curcumin. Murine macrophage RAW264.7 cells were treated with 100 μmol/l curcumin for 2 h, and then stimulated with 0.1 μ g/ml lipopolysaccharide (LPS). Serum amylase and transaminase levels were measured at 10 h after AP. TNF-α level in mouse serum and cell culture medium were detected by ELISA. Expression of PPARγ and NF-κB were analyzed by RT-PCR and Western blot. RESULTS: Curcumin significantly decreased the pancreas injury and reversed the elevation of serum amylase, ALT and AST activities and TNF-α level in mice with AP. Curcumin treatment inhibited the elevation of NF-κB-p65 in the nucleus of mouse pancreas AP group and RAW264.7 cells, but significantly increased the expression of PPARγ. GW9662 could abolish the effects of curcumin on serum levels of amylase, ALT, AST, TNF-α, and NF-κB level. INTERPRETATION & CONCLUSIONS: Our results suggest that curcumin could attenuate pancreas tissue and other organ injury by inhibiting the release of inflammatory cytokine TNF-α. These effects may involve upregulation of PPARγ and subsequent downregulation of NF-κB.